2009
DOI: 10.1371/journal.pone.0006124
|View full text |Cite
|
Sign up to set email alerts
|

ERK2, but Not ERK1, Mediates Acquired and “De novo” Resistance to Imatinib Mesylate: Implication for CML Therapy

Abstract: Resistance to Imatinib Mesylate (IM) is a major problem in Chronic Myelogenous Leukaemia management. Most of the studies about resistance have focused on point mutations on BCR/ABL. However, other types of resistance that do not imply mutations in BCR/ABL have been also described. In the present report we aim to study the role of several MAPK in IM resistance not associate to BCR/ABL mutations. Therefore we used an experimental system of resistant cell lines generated by co-culturing with IM (K562, Lama 84) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 51 publications
0
26
1
Order By: Relevance
“…The absence of any effects on E2A in A-MuLV-transformed cells in the presence of a MEK inhibitor suggests that two different pathways are regulating the induction and the repression of Cdk6 transcription. Interestingly, it has been observed that ERK2 and not ERK1 mediates resistance to STI571 in BCRAbl leukemic cells (1). This demonstrates that the Erk pathway drives proliferation in Abl-transformed cells, but our finding shows that ERK1 is important in v-Abl-transformed cells.…”
Section: Discussioncontrasting
confidence: 51%
“…The absence of any effects on E2A in A-MuLV-transformed cells in the presence of a MEK inhibitor suggests that two different pathways are regulating the induction and the repression of Cdk6 transcription. Interestingly, it has been observed that ERK2 and not ERK1 mediates resistance to STI571 in BCRAbl leukemic cells (1). This demonstrates that the Erk pathway drives proliferation in Abl-transformed cells, but our finding shows that ERK1 is important in v-Abl-transformed cells.…”
Section: Discussioncontrasting
confidence: 51%
“…86 Erk2, but not Erk1, activation may also potentiate the development of imatinibresistance. 87 Activation of the Janus kinase (Jak) and subsequent phosphorylation of several Signal Transducer and Activator of Transcription (STAT) family members has been identified in both Bcr-Abl-positive cell lines and in primary CML cells and may contribute to the transforming ability of Bcr-Abl. 88,89 Epigenetic modification Gene expression and subsequent protein function can be governed by a balance of epigenetic methylation, as well as post-translational acetylation, respectively.…”
Section: Spotlightmentioning
confidence: 99%
“…In our own laboratory, we found excessive activation of the MAP kinases (MAPKs) Erk1/Erk2 in response to TKI treatment, further supporting the notion that TKI treatment of T315I-positive CML might increase oncogenic fitness of mutant T315I beyond the TKI-naive oncogenic potential. MAPKs represent a signaling cascade able to circumvent BCR-ABL-targeted therapy, thereby promoting resistance in preclinical models [16,17]. These data add novel mechanistic explanations supporting the clinical recommendation to discontinue TKI treatment when high resistance mutations are detected not only to allow deselection of the mutant clone, but also to prevent TKI-dependent acceleration of progressive disease.…”
Section: Evolution Of Resistance Mutationsmentioning
confidence: 89%